The Wealth-Health Nexus: New Global Evidence - Jaunky, Vishal (2013)
Using a world sample of countries, this paper re-examines the U-shaped relationship between per capita GDP (wealth) and life expectancy at birth (health). Since cross-sectional dependence across countries is detected, second-generation panel unit root and cointegration tests are employed. All the variables are found to be integrated in one order as well as cointegrated. Various quadratic specifications are also employed and the hypothesis is confirmed. © 2012 International Atlantic Economic Society.